16. Effectiveness of Observe and Relate Self-Approach (Orsa) in Enhancing the Grammatical Competence: A Quantitative Study from Looc Integrated School at the Philippines - Mary Rose T. Villanueva; Glen P. Cortezano (Research Synergy Foundation, 2021)
The study determined the effectiveness of Observation Response and Self-Approach (ORSA) in improving the grammatical competence of Grade 7 learners of Looc Integrated School. This study used the quasi- experimental design and pre-test/post-test questionnaire. ORSA was used as an approach to teaching students grammar, including WHquestions, verbs, and prepositions. This was limited to selected Grade 7 students with the lowest grammatical competence. The ORSA study was taken from the name of the author itself, a new way to assess students through positive assessments that explores the learner's innate talents and skills and to reassure and encourage the development of strength in students. It is also centered on the pedagogical approaches and emphasizes the use of positive assessment as to its unique feature in evaluating students’ performance utilizing non-threatening assessments that motivated the students to develop self- efficacy and eventually become an independent learner whose competencies acquired are internationally aligned and acceptable even during this new normal in the time of the pandemic. The idea of ORSA can be anchored on Locke’s idea of reflection. Before applying the approaches, students got lower scores. After being exposed to the approaches, their mean scores increased. It can be implied that through the use of ORSA, the students think and question what they have learned through the persuasion of the teacher; they believe in themselves and in what they have learned. ORSA and K to 12, the two groups of student- participants havedifferent levels of grammatical competence. As observed in the obtained means, students exposed to ORSA achievedhigher grammatical competence as compared to students exposed to K to 12 teaching approach. This connotes that ORSA is proven effective in enhancing the grammatical competence of the students.